Avian influenza: a review - Santos, José Maurício Gonçalves dos; Rocha, Leonardo Dornelles da (Universidade Cesumar - UniCesumar, 2009)
Brazil is the third greater producer of broilers in the world, only behind United States and China. In 2006, Brazilian poultry reached the production of 9.3 million tons of chicken meat and 26.5 billion units of eggs. The Avian Influenza is a disease caused by any influenza virus type A that strikes birds, which strains are classified in low or high pathogenicity according to the capacity to provoke brand or serious disease in animals. The threat of the Avian Influenza can provoke the reduction of the consumption in Brazil’s important and traditional international customers, causing a great economic loss as well as a problem of public health, due to the risk for the humans. However, biosecurity actions must be implemented with the purpose of maintaining the sanity of the poultry breeding herds, to protect the humans and all the productive chain of a possible crisis. O Brasil é o terceiro maior produtor de frangos do mundo, atrás apenas dos Estados Unidos e da China. Em 2006 a avicultura brasileira atingiu a produção de 9,3 milhões de toneladas de carne de frango e 26,5 bilhões de unidades de ovos. A Influenza Aviária é uma doença causada por qualquer influenza vírus tipo A que acomete as aves, cujas cepas são classificadas como baixa ou alta patogenicidade, de acordo com a capacidade de provocarem doença leve ou grave nos animais. A ameaça da Influenza Aviária pode provocar a redução do consumo em importantes e tradicionais clientes internacionais do Brasil, causando um grande prejuízo socioeconômico, bem como um problema de saúde pública, devido ao risco para os humanos. Portanto, medidas de biossegurança devem ser implementadas a fim de manter a sanidade dos plantéis avícolas, proteger os humanos e toda a cadeia produtiva de uma possível crise.